Adjuvant Resveratrol Reduces Albuminuria and Serum Transforming Growth Factor-β Without Improving Glomerular Filtration Rate in Diabetic Kidney Disease: A 12-Week Randomized Controlled Trial - Eva Julita; Zulkhair Ali; Yulianto Kusnadi; Legiran (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Diabetic kidney disease (DKD) progresses through inflammation and fibrosis, with transforming growth factor-β (TGF-β) as the principal profibrotic mediator and albuminuria as a clinical surrogate of glomerular injury. Methods: We conducted a 12-week, double-blind, placebo-controlled randomized trial at Dr. Mohammad Hoesin General Hospital, Palembang, between October 2025 and January 2026 to evaluate adjuvant resveratrol on serum TGF-β, urinary albumin-to-creatinine ratio (UACR), and estimated glomerular filtration rate (eGFR). Results: Of 61 randomized adults with DKD on standard care, 54 were analyzed (resveratrol n=27 received 25 mg twice daily, derived from Polygonum cuspidatum in 95% lecithin; placebo n=27). Within the resveratrol group, serum TGF-β fell from 123.7 to 77.1 pg/mL (p=0.008) and UACR from 94.1 to 89.8 mg/g (p=0.017); within placebo, UACR rose from 81.9 to 112 mg/g (p=0.029) while TGF-β change was non-significant (p=0.428). Between-group ΔUACR was significant (p<0.001), whereas ΔTGF-β (p=0.303) and ΔeGFR (p=0.567) were not. Multivariable linear regression identified resveratrol as an independent predictor of UACR reduction (B=−394.12 mg/g; 95% CI −659.53 to −128.71; p=0.004; adjusted R²=0.129). Baseline TGF-β was the dominant predictor of ΔTGF-β (B=−0.81; p<0.001; adjusted R²=0.701), and baseline LFG stage predicted ΔeGFR (B=−4.76; p=0.021). Mild bloating was reported in 14.8% of resveratrol versus 11.1% of placebo recipients; no serious adverse events occurred. Conclusion: Adjuvant low-dose resveratrol reduces albuminuria and serum TGF-β over 12 weeks in DKD without short-term improvement in eGFR, supporting an antifibrotic biomarker signal that warrants longer trials.